ANALISIS KEBUTUHAN KAPASITAS TAMPUNGAN EMBUNG DANAU ASAM KABUPATEN DI KOTAWARINGIN BARAT - Asril Zevri (JURNAL SUMBER DAYA AIR, 2021)
This study aims to analyze the requirement for the storage capacity of Danau Asam Reservoir as one of the solutions in increasing the availability of water to meet the needs of raw water due to population growth and climate change which is quite extreme. The study was conducted in the Danau Asam Reservoir with source of water from two watersheds that flow into the reservoir, namely the Lopo River Basin with a catchment area of 11.81 Km2 and Kamat Bay with a catchment area of 12.42 Km2 in Kotawaringin Lama District in the West Kotawaringin Regency. The method used is a quantitative approach based on a simulation of the water balance between the inflow and outflow. The inflow parameter is calculated based on 90% probability reliable discharge using the FJ Mock method in two watersheds and the outflow parameter is based on the raw water demand discharge which is calculated based on the population growth rate. The result of the research indicate that the capacity of the Danau Asam Reservoir is 391,842.72 m3 to meet the raw water needs in Kotawaringin Lama District with a population of 35397 people.Keywords: Drought, Raw Water, Storage, Kotawaringin Barat